2022
DOI: 10.3389/fendo.2022.933921
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and glioma risk: A prospective multicenter study

Abstract: BackgroundThe association between glioma risk and body mass index (BMI) remains obscure.MethodsThis study aimed to assess the association between glioma risk and BMI in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. Cox proportional hazards regression was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs).ResultsThe onset of a total of 269 gliomas was observed during a median follow-up period of 12.04 years. Compared with the normal weight, overweight (HR: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The association between BMI and cancer risk remains controversial. Observational studies have shown that high BMI may either increase the risk of cancer [17][18][19] , may not be associated with cancer 20,21 , or may even decrease the risk of cancer [22][23][24] . The association between BMI and the risk of NHL has also been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…The association between BMI and cancer risk remains controversial. Observational studies have shown that high BMI may either increase the risk of cancer [17][18][19] , may not be associated with cancer 20,21 , or may even decrease the risk of cancer [22][23][24] . The association between BMI and the risk of NHL has also been inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%